I'm having trouble solving this problem. Any help is much appreciated. $\displaystyle 4sin^2(theta)+2(1-sqrt(3))(sin(theta))-sqrt(3)$
Follow Math Help Forum on Facebook and Google+
All the solutions when the expression is equal to zero, should we assume? Originally Posted by micbal9388 $\displaystyle 4\sin^2{\theta}+2(1-\sqrt{3})\sin{\theta}-\sqrt{3}$ $\displaystyle 4\sin^2{\theta}+2(1-\sqrt{3})\sin{\theta}-\sqrt{3} = 0 \Rightarrow \left(2\sin{\theta+1}\right)\left(2\sin{\theta}-\sqrt{3}\right) = 0 \Rightarrow ...$
View Tag Cloud